2020
DOI: 10.1080/09712119.2020.1848846
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional parameters of eggs from laying hens fed with flaxseed meal or mixture with rapeseed meal or rice bran

Abstract: The effect of flaxseed meal or mixture with rapeseed meal or rice bran on the performance and nutritional quality of the eggs was investigated in a 6-week feeding trial on 120, Tetra SL layers (38 weeks). The hens, 4 groups (30 hens/group; 2 birds/cage) were feed with a basal diet (C); flaxseed meal (5%; E1); flaxseed meal-rapeseed meal (2.5%; 10%; E2) and flaxseed meal-rice bran (2.5%; 10%; E3). At the end of the trial, 18 eggs/group were collected to determine the egg quality and were assayed for the nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Vlaicu and Panaite [60] demonstrated the effectiveness of pumpkin seed sterols in reducing egg yolk cholesterol. In agreement with the conclusions of our study, the data available in the specialized literature show that supplementing the diets of laying hens with flax seeds [61,62], hemp seeds [11], and rapeseed [63] led to a decrease in cholesterol concentration in yolks. However, other studies reported that the fat source in the diets of hens does not influence the level of cholesterol in egg yolks [64].…”
Section: Egg Yolk Cholesterol Contentsupporting
confidence: 93%
“…Vlaicu and Panaite [60] demonstrated the effectiveness of pumpkin seed sterols in reducing egg yolk cholesterol. In agreement with the conclusions of our study, the data available in the specialized literature show that supplementing the diets of laying hens with flax seeds [61,62], hemp seeds [11], and rapeseed [63] led to a decrease in cholesterol concentration in yolks. However, other studies reported that the fat source in the diets of hens does not influence the level of cholesterol in egg yolks [64].…”
Section: Egg Yolk Cholesterol Contentsupporting
confidence: 93%
“…An analysis investigating the effects of various RRC treatments on the cholesterol content of eggs produced rather surprising results. Panaite et al [ 78 ] demonstrated that diets rich in PUFAs can effectively reduce egg cholesterol levels. In the present study, the eggs produced in groups RRC, HRC, and FRC were characterized by the significantly lowest levels of hypercholesterolemic FAs and the highest levels of hypocholesterolemic Fas, which is why egg cholesterol levels were expected to decrease in all experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AI and TI show to what extent individual fatty acids affect the increase in pathogenic risk of atheroma and/or thrombi that directly affect human health. Eggs with lower SFA/PUFA ratios exhibit lower AI, TI, and HHI [20,27,30]. El-Wakf et al [31] reported that consumption of eggs with lower AI and TI reduced the risk of atherosclerosis, and Hosseini-Vashan et al [32] and Watson et al [33] stated that low TI reduced atrial fibrillation.…”
Section: Egg Lipid Indexesmentioning
confidence: 99%